2022
DOI: 10.3389/fcvm.2022.1073069
|View full text |Cite
|
Sign up to set email alerts
|

Markers of extracellular matrix remodeling and systemic inflammation in patients with heritable thoracic aortic diseases

Abstract: BackgroundIn approximately 20% of patients with thoracic aortic aneurysms or dissections a heritable thoracic aortic disease (HTAD) is suspected. Several monogenic connective tissue diseases imply high risk of aortic disease, including both non-syndromic and syndromic forms. There are some studies assessing inflammation and extracellular matrix remodeling in patients with non-hereditary aortic disease, but such studies in patients with hereditary diseases are scarce.AimsTo quantify markers of extracellular mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“… 3 The authors rationalize that this endoribonuclease might be involved in Marfan syndrome aortopathy because (1) its expression is regulated by TGF-β, a crucial aggravating driver of aortopathy, 4 (2) it is a negative regulator of oxidative stress, another known actor in TAAD progression, 5 and (3) its intrinsic anti-inflammatory properties, where the role of inflammation is becoming increasingly more evident in the progression of the aortopathy. 6 …”
Section: Main Textmentioning
confidence: 99%
“… 3 The authors rationalize that this endoribonuclease might be involved in Marfan syndrome aortopathy because (1) its expression is regulated by TGF-β, a crucial aggravating driver of aortopathy, 4 (2) it is a negative regulator of oxidative stress, another known actor in TAAD progression, 5 and (3) its intrinsic anti-inflammatory properties, where the role of inflammation is becoming increasingly more evident in the progression of the aortopathy. 6 …”
Section: Main Textmentioning
confidence: 99%
“…In another study, Seim et al . [ 30 ] conducted research on plasma extracellular matrix (ECM) remodeling markers in patients with heritable thoracic aortic disease (HTAD) by employing an enzyme-linked immunosorbent assay. They found that all subgroups of HTAD patients have elevated levels of MMP-9, indicating its role as a mediator of inflammation and ECM remodeling.…”
Section: Causes Associated With Vascular Remodelingmentioning
confidence: 99%